The Effect Of Online Customer Reviews And Prices On Purchase Intention On Madam Royale Products - Maeza Rike Nabila Maeza; Tias Andarini Indarwati (Lavish Opulent Education, 2025)
This study aims to determine the influence of Online Customer Reviews and Prices on consumer Purchase Intention on Madam Royale detox drink products. This study uses a quantitative approach with descriptive and causal types of research. The sample in this study is 110 Generation Z respondents who were selected through the purposive sampling method. The analysis technique used was multiple linear regression with the help of SPSS version 26. The results of the study show that simultaneously, Online Customer Reviews and Prices have a significant effect on Purchase Intention. However, partially, only the Price variable had a positive and significant effect, while Online Customer Reviews had no significant effect. These findings indicate that the perception of appropriate price determines consumer purchase intent more than online reviews. Therefore, the right price strategy is considered more effective in increasing interest in buying products among Generation Z.